Near misses and unsafe conditions reported in a Pediatric Emergency Research Network. Issue 9 (2nd September 2015) - Ruddy, Richard M; Chamberlain, James M; Mahajan, Prashant V; Funai, Tomohiko; O'Connell, Karen J; Blumberg, Stephen; Lichenstein, Richard; Gramse, Heather L; Shaw, Kathy N; ,
Abstract : Objective: Patient safety may be enhanced by using reports from front-line staff of near misses and unsafe conditions to identify latent safety events. We describe paediatric emergency department (ED) near-miss events and unsafe conditions from hospital reporting systems in a 1-year observational study from hospitals participating in the Pediatric Emergency Care Applied Research Network (PECARN). Design: This is a secondary analysis of 1 year of incident reports (IRs) from 18 EDs in 2007–2008. Using a prior taxonomy and established method, this analysis is of all reports classified as near-miss (events not reaching the patient) or unsafe condition. Classification included type, severity, contributing factors and personnel involved. In-depth review of 20% of IRs was performed. Results: 487 reports (16.8% of eligible IRs) are included. Most common were medication-related, followed by laboratory-related, radiology-related and process-related IRs. Human factors issues were related to 87% and equipment issues to 11%. Human factor issues related to non-compliance with procedures accounted for 66.4%, including 5.95% with no or incorrect ID. Handoff issues were important in 11.5%. Conclusions: Medication and process-related issues are important causes of near miss and unsafe conditions in the network. Human factors issues were highly reported and non-compliance with established procedures was very common, and calculation issues, communications (ie, handoffs) and clinical judgment were also important. This work should enable us to help improve systems within the environment of the ED to enhance patient safety in the future.